Survey of Skull Base Surgeons' Approach to Carcinomas Involving the Cavernous Sinus - Mott, Nicole M.; Ryder, C. Yoonhee; Snyderman, Carl H.; McKean, Erin L. (Journal of Neurological Surgery Part B: Skull Base, 2022)
Objectives Carcinomas involving the cavernous sinus are challenging to resect without compromising important neurovascular structures. Given the morbidity and mortality of these operations, radiotherapy, chemotherapy, and immunotherapy are more often utilized. Although limited to case reports and small series, radical resection of the cavernous sinus has been proposed. We aimed to study surgeons' willingness to perform cavernous sinus exenteration (CSE) under different clinical scenarios.Design, Setting, Participants, Main Outcome Measures We conducted an online survey from April to July 2021 among members of the Skull Base Congress and the North American Skull Base Society. Descriptive statistics were used to analyze the main outcome measure of willingness to perform CSE.Results The analytic sample (n = 112) included 54% otolaryngologists and 43% neurosurgeons. Eighty-six percent practiced in an academic setting. Surgeons' willingness to perform CSE was low (6–16% under different clinical scenarios), citing a belief that they could not obtain oncologic margins and the procedure's morbidity. Forty-five percent had at least one patient undergo CSE with 72% of patients surviving no more than 2 years.Complications included chronic intractable pain, cerebrospinal fluid leak, cerebrovascular accident, and/or intraoperative/postoperative death within 30 days. Sixty percent agreed that the availability of immunotherapy and genomic sequencing has affected their willingness to offer CSE.Conclusion Overall, most of the surgeons surveyed were unwilling to offer CSE for carcinomatous cavernous sinus invasion, whether for primary disease or recurrence. Given the rarity of these tumors and the limited data on CSE, these results may provide more information for clinicians and patients for these treatment decisions.
Keywords: carcinoma; cavernous sinus; cavernous sinus resectioncavernous; cavernous sinus exenteration